User participation in mental healthcare in Suriname: the implementation of a client council - De Freitas, Cláudia (2013)
User participation in mental healthcare has increased considerably in many countries around the world in the past decades. However, users’ voices are still incipient in other countries. This was the case of Suriname where user participation emerged just recently with the creation of a client council at the national mental healthcare service (PCS). The PCS client council was implemented as a result of a project involving a transnational partnership between stakeholders in Suriname and the Netherlands. Employing a qualitative research approach, this paper examines the client council implementation process and analyses stakeholders’ expectations for its future performance, benefits and disadvantages. The paper concludes that the client council offers a space from which traditionally excluded users can renegotiate their identities, develop new skills, influence care provision and exercise their citizenship. For genuine participation to emerge, however, it will be necessary to invest in effecting cultural and organisational change in mental healthcare, tackling power differentials between care providers and users, resourcing the council and reducing the stigma attached to mental illness. Transparency, consultation, negotiation and full collaboration are also identified as key elements to foster productive transnational partnerships, especially when they involve stakeholders belonging to countries with a colonial history.